Od fanów dla fanów. Komentarze serialowe jako nowe zjawisko komunikacyjne - Kaproń-Charzyńska, Iwona; Kamper-Warejko, Joanna (Przestrzenie Teorii, 2019)
The article addresses the question of the Internet activity of anonymous amateur translators and fans’ translations of subtitles for series using the example of Korean dramas. The authors focus on analysing the genre of commentary in the audiovisual narrative – TV series. The authors put forward the thesis that the synthetic model of communication in the Internet stimulates communication activity, which affects the transformation of language patterns. Series commentary has been considered to be a new type of genre pattern functioning in the media. What is novel is the kind of cultural text within which a given commentary appears. It may be compared to a commentary which is an explanation, a supplement to the text it refers to. It may also be compared to a more recent pattern – the Internet commentary.